Pengembangan Sistem Informasi Rapor Kesehatan Online - Anita Widiastuti; Rusmini Rusmini; Sumiyati Sumiyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to build an information system to facilitate data input activities, surveillance, and monitoring of adolescent health. This research method is Research and Development (R&D). This study is an information system recording the results of filling out multiple intelligence questionnaires, anthropometric measurements, and vital signs of each individual at a web-based youth posyandu. The information system development method uses the Systems Development Life Cycle (SDLC) approach. The system for recording adolescent measurements includes weighing, measuring height, calculating BMI, measuring blood pressure, measuring upper arm circumference and abdominal circumference, and checking anemia for adolescent girls clinically every month. In conclusion, this information system is a solution to the existing documentation problems in implementing the youth posyandu. There is still limited access to my health report card for recording adolescent health. Keywords: Recording, Youth Posyandu, Information System